2001
DOI: 10.1159/000047871
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Defined Protein-Free in vitro Culture of Mammalian Embryo Does Not Restrict Its Developmental Potential for Differentiation of Skin Appendages

Abstract: In a unique serum- and protein-free chemically defined in vitro culture model of postimplantation mammalian development the epidermis differentiates regularly, although the differentiation of other tissues is impaired due to the lack of the serum. The present study in that model was done to estimate more carefully the degree of epidermal differentiation in defined media supplemented with some growth- or differentiation-stimulating substances. The main objective was to discover by grafting in vivo to the richer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Our results obtained previously regarding transplantation under the kidney capsule of in vitro cultivated gastrulating embryos-proper showed that this site is optimal for the continuation of chondrogenesis, osteogenesis, neurogenesis, and development of skin appendages. In vivo results also reflected results obtained by previous cultivation in vitro (Belovari et al, 2001;Bulic-Jakus et al, 2001).…”
Section: Introductionsupporting
confidence: 84%
“…Our results obtained previously regarding transplantation under the kidney capsule of in vitro cultivated gastrulating embryos-proper showed that this site is optimal for the continuation of chondrogenesis, osteogenesis, neurogenesis, and development of skin appendages. In vivo results also reflected results obtained by previous cultivation in vitro (Belovari et al, 2001;Bulic-Jakus et al, 2001).…”
Section: Introductionsupporting
confidence: 84%
“…The classical ectopic in vivo transplantation model used here (9), confirmed its value for this particular developmental study dealing with embryonic epiglottis, because 17-days-old epiglottis survived well and its differentiation proceeded towards the mature elastic cartilage. Subcapsular kidney space has been exploited extensively before for investigation of developmental potential of a number of embryonic tissues such as the embryonic shield (19), single germ layers (20), retina (21), lacrimal gland (22), mandible (23) and lensectomized eyes (24,25). Results obtained with epiglottis are in concordance with those studies because development always progressed and tissues could exert at least a part of their full developmental potential even if pre-cultivated in poor metabolic conditions such as chemically defined media without any proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained with epiglottis are in concordance with those studies because development always progressed and tissues could exert at least a part of their full developmental potential even if pre-cultivated in poor metabolic conditions such as chemically defined media without any proteins. The reason for this lies probably in the optimal vascularization of the kidney capsule that provides an optimal microenvironment (19).…”
Section: Discussionmentioning
confidence: 99%
“…As shown previously, by subsequent isotransplantation of the precultivated embryo-derived teratoma to the metabolically richer environment in vivo for another 14 days, the residual potential for further growth or differentiation (e.g., of skin appendages, bone, neural tissue, and even organotypic structures) or the restriction of such potential was assessed [32,33]. A similar teratoma assay in rodents in vivo is used to confirm pluripotency [34] or discover a residual potential for malignant transformation of various cells precultivated in vitro for regenerative medicine purposes [12,35].…”
mentioning
confidence: 99%